(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This study examines the human resource management (HRM) practices in public and privatehospitals and compares their approaches in achieving organizational goals and enhancing patient care.The findings reveal that both sectors recognize the importance of effective HRM practices, but facedistinct challenges and exhibit different strategies. Public hospitals often encounter resource constraintsand bureaucratic structures, leading to difficulties in talent acquisition, retention, and performancemanagement. In contrast, private hospitals benefit from greater flexibility and autonomy, enabling themto implement innovative and strategic HRM practices, including competitive compensation packages,performance-based incentives, and robust talent management systems. Private hospitals generallyexhibit more progressive and adaptable HRM practices, positioning them to attract and retain top talentand provide higher quality healthcare services. Bridging the gap between public and private hospitals interms of HRM practices is crucial to enhancing the overall performance of public hospitals. Furtherresearch should focus on developing strategies to overcome constraints faced by public hospitals andpromote the adoption of effective HRM practices to improve healthcare outcomes.